EFFECT OF MATERIALISM, PUBLIC SELFCONSCIOUSNESS AND SELF-ESTEEM ON CONSPICUOUS CONSUMPTION AMONG GENERATION Z CONSUMERS - Emamdin Moustabshirah; Jugindar Singh Kartar Singh; Wong Huey Wern (International Journal of Accounting, Finance and Business, 2022)
Generation Z consumers are heading into work force and will be the primary drivingforce in the consumption growth of luxury products and services. However, despite a dearth ofstudies on the determinants of conspicuous consumption among Gen Z in Malaysia, still theeffect of conspicuous consumption on materialism, public self-consciousness, and self-esteemremains unclear. This quantitative research surveyed 208 Gen Z using self-administeredquestionnaires in Malaysia. The philosophy of Positivism was adopted. Primary data wascollected and results were scrutinized through the SPSS software that generated Descriptiveand inferential statistics. Research findings revealed that materialism and self-esteem hadsignificant impact on conspicuous consumption compared with public self-consciousness. Thus,public self-consciousness was not a significant predictor of conspicuous consumption. Theresearch findings knowledgeably benefited retailers, marketers and advertisers who nowunderstand better why prioritising materialism and self-esteem rather than public selfconsciousness.